Data Journalism and Fact-Checking: Enhancing Credibility in the Information Age - M R RAMESH (Journal of Advanced Research in Journalism & Mass Communication, 2024)
This research paper explores the intersection of data journalism and fact-checking, examining their pivotal roles in promoting accuracy and credibility in the contemporary media landscape. As the digital era accelerates information dissemination, the need for robust journalistic practices has become paramount. Data journalism harnesses the power of data analysis and visualization, while fact-checking serves as a critical tool for verifying information. Together, they contribute to a more informed and accountable society. This paper delves into the methodologies, challenges, and impact of integrating data-driven reporting with rigorous fact-checking processes.